Stopping the War in Sudan: Civilian actors, not just the parties to the conflict, should lead the peace negotiations - Hager Ali; Gerrit Kurtz (Stiftung Wissenschaft und Politik (SWP), 2023)
Sudan's two main security forces are fighting each other. A swift military outcome is not to be expected in view of the relatively balanced power between the Sudanese Armed Forces (SAF) and the Rapid Support Forces (RSF). This strategic stalemate means that the chances for successful mediation are not hopeless. For this to happen, however, Sudan's international partners would have to abandon the approach that dominated negotiations for decades, namely giving violent actors a leading role in negotiations. Civilian actors formed a broad anti-war coalition that should set the tone for peace talks from the very beginning. This could well be in the interest of the parties to the conflict, as they will need a third actor to arbitrate their relationship in the future. The German government should strive for stronger coordination of the international mediation approaches under civilian leadership from Sudan, while the European Union (EU) should initiate constrains on the financial leeway of Sudan's violent actors.
Keywords: 320; Sudan; War; Omar al-Bashir; Sudanese Armed Forces (SAF); Rapid Support Forces (RSF); General Abdel Fattah al-Burhan; General Mohamed Hamdan Dagalo (Hemedti)